The puppy kindergarten : the new science of raising a great dog - Hare, Brian, 1976-; Woods, Vanessa, 1977- (Random House, 2024)
"When husband and wife scientists Brian Hare and Vanessa Woods fell in love with a trained service dog named Congo, they wanted to understand what made him such a great companion. Given that there hadn't been a large-scale study of puppy development since 1950, they decided to start one, inviting generations of Labrador and Golden Retriever puppies and dozens of student volunteers to come to their lab at Duke University, and the Puppy Kindergarten was born. When and how do puppies develop key cognitive skills such as self-control or cooperative communication? Using the same kinds of cognitive tests and games that have become standard for understanding human infant development, they initially wanted to know if they could predict which qualities would make puppies grow up to be great assistance dogs. But they quickly realized that these special dogs have a lot to tell us about how all dogs navigate the world, solve problems, and learn from the people around them. Even the smartest dogs can't figure out how to make the water stay in their bowl, but they can read our gestures and respond to our emotions in a way that no other species can. Introducing us to the many puppies who contributed to this research and synthesizing findings from cognitive neuroscience, psychology, and evolutionary anthropology, this delightful, informative book will teach readers how puppies begin to develop abilities that allow them to succeed as adults and flexibly solve problems, giving us a new window into who our dogs are, how they see the world, and the amazing things they can do"--